Understanding of boost-PFC circuit design for low cost electronic ballast - Dangeam, Sirichai; Boonchiam, Paisan (Frontiers in Engineering Innovation Research, 2005)
This paper presents a simple design of Power Factor Correction (PFC) circuit for using in electronic ballasts circuit based on the boost topology which the suitable value of inductor, capacitor and switching frequency are selected. The improved design method has also been developed for increasing power factor and reducing harmonics of the system. The experiments and satisfactory results are demonstrated and presented.